KERJASAMA KEPOLISIAN NEGARA REPUBLIK INDONESIA (POLRI)- AUSTRALIAN FEDERAL POLICE (AFP) SEKTOR CAPACITY BUILDING DALAM PENANGGULANGAN TINDAK PIDANA CYBER CRIME DI INDONESIA PERIODE 2012-2014 - Burhansyah A, Encik Mochammad; Utomo, Tri Cahyo; Putranti, Ika Riswanti (Journal of International Relations, 2016)
In the current era of globalization is growing at a rapid advancesin technology. One proof of the technological advances with theinternet. But technological advancements, giving a negative effectof the emergence of world crime (cyber crime). In the category ofcyber crime, Indonesia is one country under threat of cyber crimein the world. To deal with and overcome this, the IndonesianNational Police (INP) formed a partnership with the AustralianFederal Police (AFP) in preventing the crime of cyber crime. Thecooperation is realized in the form of increased capacity (capacitybuilding) provided by AFP against police personnel through afoundation called the Jakarta Centre for Law EnforcementCooperation (JCLEC). As a result of cooperation between thePolice-AFP gives relatively good results. However, the handling ofthe case is still far from the expected that in 2012 as many as 86cases of unresolved cases, as many as 115 cases in 2013 andJanuary-June 2014 as many as 94 cases.